(3GdGYJHGQ aj fSH GdfHj GdoeNJGQ hGdJYQja HCRhGLg hChdGOgs - (3CMeO Hf eMeO Hf CHj GdbGSe Hf CMeO Hf YHO GdQMef Gdecj GdYTeGhj,J (B1142 (3g` s ((3eMeO Hf eHGQc GdOcGdj s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdehLhO GdHGbi GdeYHhO s
(3BNQgG (B:s
(3ef TGgO Edi TGgO hef YOd Edi YOd hef bGV Edi bGV s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B32 (3Hs
(3hbO JZjQ fhY GdNW GdeSJNOe aj HYV UaMGJgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B242 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B70s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B421 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B35 s
Keywords: (3GdJGQjNs